Konektor Masker : Peluang Usaha Di Balik Pandemi - Novi Tri Putri Putri; Izharudin (UNIB Press, 2022)
The Covid-19 pandemic in Indonesia since March 2020 has had a negative impact on the community's economy in fullfil the needs of life and working. The decline in community activity has an impact on the business sector, especially food stalls, street vendors, small shops and others. The use of masks has become a lifestyle due to the corona virus pandemic creating business opportunities related to women's accessories, namely mask connectors. The mask connector is the product chosen to be given skills in this empowerment activity so that the community can take advantage of this business opportunity as an effort to take advantage of business opportunities during the pandemic and increase family income.